Intravenous anesthetics have differential effects on human potassium channels - Tao Ying; Yao Kejie; Wu Jing; Xu Tian; Lin Junhui; Qin Yi; Su Diansan; Cai Shiqing; Yu Weifeng; Chen Xuemei (Acta Biochimica et Biophysica Sinica)
General anesthetics are widely used in the clinic and greatly promote the development of surgery. However, the incidence of cardiovascular and respiratory complications caused by general anesthetics is still high, and the underlying mechanisms remain incompletely understood. Potassium channels are widely expressed in the heart and blood vessels and participate in regulating blood pressure, heart rate, and other physiological parameters. Whether they are directly affected by intravenous general anesthetics is unclear. Here, we independently express four classes of potassium channels, TASK-1, TASK-3, Kv1.5, Kv2.1, Kir2.1, SK1 and SK3, in Xenopus oocytes. The effects of propofol, pentobarbital and ketamine on these channels are evaluated by their current change. We find that propofol and ketamine potentiate TASK-3 and SK3 current respectively, while pentobarbital and ketamine inhibit SK1 current. To identify the key residues in TASK-3, SK1 and SK3 that interact with intravenous anesthetics, we predict homology models of the three channels and perform molecular docking simulations. The results show that propofol forms a hydrogen bond with Q126 of TASK-3, ketamine forms a hydrogen bond with S290 of SK1 and S467 of SK3, while pentobarbital forms hydrogen bonds with S330 and T358 of SK1. As these potassium channels are closely related to respiratory system regulation, cardiac rhythm and vasodilation, our study provides a new perspective for further study on the mechanism of general anesthetics-induced respiratory and circulatory side effects.